2019
DOI: 10.3390/molecules24193611
|View full text |Cite
|
Sign up to set email alerts
|

Polyamidoamide Dendrimers and Cross-Linking Agents for Stabilized Bioenzymatic Resistant Metal-Free Bovine Collagen

Abstract: The work reports the use of polyamidoamine dendrimers (PAMAM) and a cross-linking agent, 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide/N-hydroxysuccinimide (EDC/NHS) or 4-(4,6-dimethoxy[1,3,5]triazin-2-yl)-4-methyl-morpholinium chloride (DMTMM), for the thermal stabilization of dermal bovine collagen. The efficiency of EDC/NHS/PAMAM and DMTMM/PAMAM in the cross-linking of collagen is correlated to the increase of the collagen shrinkage temperature (Ts), measured by differential scanning calorimetry (DSC). An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…In this frame, dehydro-condensation reactions are a well-known and consolidated protocol for the synthesis of amides, although toxic dehydro-condensation agents are often used to promote the reaction [ 17 , 19 ]. For example, carbodiimides such as dicyclohexylcarbodiimide (DCC) or 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide chlorohydrate (EDC) employed in combination with N -hydroxysuccinimide (NHS), have frequently been employed for the scope ( Figure 1 ) [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this frame, dehydro-condensation reactions are a well-known and consolidated protocol for the synthesis of amides, although toxic dehydro-condensation agents are often used to promote the reaction [ 17 , 19 ]. For example, carbodiimides such as dicyclohexylcarbodiimide (DCC) or 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide chlorohydrate (EDC) employed in combination with N -hydroxysuccinimide (NHS), have frequently been employed for the scope ( Figure 1 ) [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this prospective, quaternary ammonium salts of 2-halo-4,6-dialkoxy-1,3,5-triazines, e.g., 4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride (DMTMM(Cl)), (see Figure 2 ), represent a valid alternative for the formation of amide bonds both in organic and water solvent [ 20 , 21 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. In the last years, DMTMM(Cl), commonly known as DMTMM, has found many applications as dehydro-condensation agent for the synthesis of amides and esters [ 36 , 40 ], collagen cross-linking [ 7 , 21 , 38 ], preparation of carboxymethylcellulose based films [ 39 ], amine grafting on hyaluronan [ 20 , 40 , 41 ], and peptide synthesis [ 42 ]. Additionally, the synthesis of a library of 2-(4,6-dimethoxy-1,3,5-triazinyl)trialkyl ammonium salts (DMT-Ams(X), X: Cl − or ClO 4 − ) and their activity as dehydro-condensation agents for the synthesis of amides, has been reported by Kunishima et al [ 43 ] ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Glutaraldehyde is toxic, whereas EDC is a zero-length crosslinker i.e., it can be successfully removed either by dialysis or centrifugation from the system. Reports have also suggested that cross-linking PAMAM with collagen is a better way for safe biomedical applications [63,64]. As the dental matrix is predominately made up of collagen Type I [65], we activated the carboxylic group amino acids present in collagen and was allowed to form a covalent amide bond with the amine group of the dendrimer.…”
Section: Preparation and Characterization Of Silver Nanoparticles (Agnps)mentioning
confidence: 99%
“…Triazine tanning agents are gaining increasing interest in recent years as valid, environmentally friendly alternatives that are metal-, formaldehyde-, and phenol-free [ 15 , 29 , 30 , 31 , 32 ]. Presently the leather industry is suffering from restrictions due to the ECHA-REACH regulation, which has significantly limited the variety of chemical substances allowed as tanning agents.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has long been involved in the study of innovative, sustainable processes for the industry and leather processing [ 29 , 35 , 36 ]. In the last years, 4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methyl-morpholinium chloride (DMTMM) has found many applications as dehydro-condensation agent for collagen cross-linking [ 29 , 30 , 37 ], amine grafting on hyaluronan [ 38 ], amide, and peptide synthesis [ 39 , 40 , 41 , 42 , 43 ]. DMTMM is a very efficient cross-linking agent which promotes the reaction between carboxylic and amine groups in mild reaction conditions to form amides.…”
Section: Introductionmentioning
confidence: 99%